Scaling social innovation through cross-sector social partnerships : driving optimal performance - Pittz, Thomas G.; Intindola, Melissa L. (Emerald Publishing Limited, 2021)
This book is designed to illuminate the features of cross-sector partnerships that make them powerful vehicles to drive social change. Partnerships across market sectors, involving for-profit, non-profit, and government entities, work because they leverage the advantages of each type of organization to arrive at novel solutions to social problems. Unlike previous work that has discussed cross-sector, multi-sector, or public-private partnerships at a conceptual level, this book scours the existing literature and explores real-life examples to demonstrate the practical characteristics that render these partnerships effective at tackling obstreperous social problems. The authors delve into the key formative features of cross-sector partnerships such as leadership, motivation, cooperative capabilities, and arrive at distinct characteristics that drive performance. The authors lay out a succinct roadmap for creating and maintaining viable cross-sector social partnerships, with instructive real-life examples that highlight how these partnerships can be executed effectively.
Includes index.
Keywords: Public-private sector cooperation.; Social responsibility of business.; Business & Economics -- Decision-Making & Problem Solving.; Business strategy.; elektronické knihy; electronic books